Correction: Passive hypothermia (≥35 - <36°C) during transport of newborns with hypoxic-ischaemic encephalopathy. - Aurélie Sellam; Noëlla Lode; Azzedine Ayachi; Gilles Jourdain; Jean-Louis Chabernaud; Stéphane Dauger; Peter Jones (PLoS ONE, 2017)
[This corrects the article DOI: 10.1371/journal.pone.0170100.].